Communication, Motivation, and Exemplarity: Building Performance Effectiveness Through a Family-Oriented Leadership Style - Puspitasari, Nurma; Ayustia, Rissa (Universitas Pattimura, 2025)
This study explores the influence of family-oriented leadership on employee performance effectiveness at the National Amil Zakat Institution of Membangun Keluarga Utama (LAZ MKU) in Yogyakarta. Employing a qualitative approach, data were collected through in-depth interviews, direct observation, and document analysis, with triangulation of sources used for validation. The findings reveal that family-oriented leadership—marked by transparent communication, participative decision-making, exemplary behavior, and motivational strategies rooted in familial values—significantly enhances employee performance. A structured evaluation system based on Key Performance Indicators (KPIs) supports continuous performance monitoring and development. The implementation of this leadership model has resulted in employees demonstrating high discipline, strong initiative, and consistent achievement of performance targets. Notably, the study identifies a sense of ownership, solidarity, and commitment among staff as key outcomes of the applied leadership approach. The novelty of this research lies in its integration of a culturally grounded, family-oriented leadership framework within a non-profit organizational setting—an area underexplored in management literature. The study contributes to the advancement of social sciences and humanities by emphasizing the role of local values in shaping effective organizational leadership. It recommends leadership development programs, digital communication enhancements, and reward system implementation as strategic steps for non-profit organizations aiming to adopt similar models.